Management accounting practices in many countries around the world: A review of the literature - Syamsul Azri, Abdul Rahman; Mazuri, Abd Ghani; Abdelghani, Ahmed (2019)
Preface: Throughout the last decade and a half, management accounting practices (MAPs) studies have garnered increasing attention from researchers and professionals in accounting across several countries, particularly those that are in the process of transitioning. This may be attributed to many reasons, among the top of which is the increase in the domestic and foreign markets competitiveness, globalization effects, declines in profit margins and increase in the inputs owing to the energy and economic crisis. Purpose: This paper attempts to review studies dedicated to management accounting practices (MAPs) in several countries. Design/Methodology/Approach: Data was gathered from prior literature and tabulated, based on title, year and country context of the study and the sample size as well as the publication journal. Findings: The findings showed that researchers have been extensively dedicating their efforts to examining accounting management practices in various sectors, particularly in manufacturing. In the Malaysian context, five relevant studies were conducted, one in 2011, and two each in 2015 and 2017. Value: This study is expected to contribute to the gap in MAPs studies in several countries and provide an invaluable framework for future studies to adopt.